1997
DOI: 10.1016/s0035-9203(97)90394-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities in patients bitten by taipans (Oxyuranus scutellatus canni) and other elapid snakes in Papua New Guinea

Abstract: Envenoming by a number of species of snake may affect the myocardium or cause electrocardiographic changes; several different mechanisms have been proposed. In a prospective study of snake bite in Papua New Guinea, electrocardiographic changes were observed in 36 of 69 patients (52%) envenomed by the taipan (Oxyuranus scutellatus), 2 of 6 (33%) envenomed by death adders (Acanthophis sp.) and one envenomed by the brown snake (Pseudonaja textilis). Septal T wave inversion and bradycardias, including atrioventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…The results of this investigation clearly indicate that NS venom is cardiotoxic, and this is likely true of cobra venoms in general, given their similarities in composition [7]. This is interesting because cobra venoms, as used here, are not mainly known for their cardiotoxic activity, though studies have been carried out over the years to suggest this [9,53,54]. It has been argued that most cases of cardiac instability by cobra envenomation are actually caused by hypoxia or acidosis secondary to respiratory paralysis.…”
Section: Discussionmentioning
confidence: 57%
“…The results of this investigation clearly indicate that NS venom is cardiotoxic, and this is likely true of cobra venoms in general, given their similarities in composition [7]. This is interesting because cobra venoms, as used here, are not mainly known for their cardiotoxic activity, though studies have been carried out over the years to suggest this [9,53,54]. It has been argued that most cases of cardiac instability by cobra envenomation are actually caused by hypoxia or acidosis secondary to respiratory paralysis.…”
Section: Discussionmentioning
confidence: 57%
“…MI as a result of snake envenomation has been reported (116 ), with rare occurrences of non-AMI increases in cTn related to snake envenomation (117 ). In a prospective study of 45 patients who complained of snake bite, none were found to have increased cTn (118 ).…”
Section: Envenomationmentioning
confidence: 99%
“…3 Envenomings by this large elapid snake are characterized by minor local effects and severe systemic manifestations, including irreversible flaccid paralysis, coagulopathy associated with systemic spontaneous bleeding, myotoxicity, acute kidney injury, and cardiac damage. [2][3][4][5][6] The therapy for envenomings by O. scutellatus in PNG is based on the intravenous administration of either CSL Polyvalent Antivenom or CSL Taipan Antivenom (both manufactured by bioCSL Limited in Melbourne, Victoria, Australia; CSL). They are F(ab') 2 antivenoms generated by pepsin digestion and ammonium sulphate precipitation of plasma of hyperimmunized horses.…”
Section: Introductionmentioning
confidence: 99%